Mastering Students’ Speaking Skill using Inquiry Online Project-based Strategy - Muna, Faizul; Aziz, Imam Nur (Indonesian Journal of Instructional Media and Model, 2021)
This study focuses on the use of an online learning research project focused on students' speaking skills. It is an innovative and practical approach that can develop students to solve a problem by thinking critically. This study aimed to determine the effect of using inquiry project-based learning on students' speaking skills. The research was conducted at MTs Mambaus Sholihin Gresik in class VII Q. To determine whether inquiry-project based online learning is effective or not, researchers used a pre-experimental method, where the statistical formula of the t-test calculates information. The research result is that the pre-test's mean was 83.9189, and the norm of the post-test was 88.5135. The results showed that inquiry-project based online learning projects had a positive effect on students' speaking achievement. It means that there is a large effect, with a substantial difference in student scores before and after treatment. Thus it can be concluded that inquiry-project-based online learning is recommended to promote students' speaking skills.